Atherogenic Cytokines Regulate VEGF-A-Induced Differentiation of Bone Marrow-Derived Mesenchymal Stem Cells into Endothelial Cells - Izuagie Attairu Ikhapoh; Christopher J. Pelham; Devendra K. Agrawal (Stem Cells International)
Coronary artery stenting or angioplasty procedures frequently result in long-term endothelial dysfunction or loss and complications including arterial thrombosis and myocardial infarction. Stem cell-based therapies have been proposed to support endothelial regeneration. Mesenchymal stem cells (MSCs) differentiate into endothelial cells (ECs) in the presence of VEGF-A in vitro. Application of VEGF-A and MSC-derived ECs at the interventional site is a complex clinical challenge. In this study, we examined the effect of atherogenic cytokines (IL-6, TNFα, and Ang II) on EC differentiation and function. MSCs (CD44+, CD73+, CD90+, CD14−, and CD45−) were isolated from the bone marrow of Yucatan microswine. Naïve MSCs cultured in differentiation media containing VEGF-A (50 ng/mL) demonstrated increased expression of EC-specific markers (vWF, PECAM-1, and VE-cadherin), VEGFR-2 and Sox18, and enhanced endothelial tube formation. IL-6 or TNFα caused a dose-dependent attenuation of EC marker expression in VEGF-A-stimulated MSCs. In contrast, Ang II enhanced EC marker expression in VEGF-A-stimulated MSCs. Addition of Ang II to VEGF-A and IL-6 or TNFα was sufficient to rescue the EC phenotype. Thus, Ang II promotes but IL-6 and TNFα inhibit VEGF-A-induced differentiation of MSCs into ECs. These findings have important clinical implications for therapies intended to increase cardiac vascularity and reendothelialize coronary arteries following intervention.